Development of Youth Liturgy as a Means of Character Education in Local Churches - Tamangunde, Natalia Andriana (Peneliti.net, 2025)
The development of youth liturgy in local churches plays a strategic role as a means of character education, significantly contributing to the formation of young people’s personality and spirituality. Liturgy functions not only as a religious ritual but also as a faith experience that holistically shapes moral, social, and spiritual values. This study aims to explore in depth how youth liturgy can be optimized as an effective medium for character formation through meaningful and contextual worship experiences. The research employs a qualitative descriptive approach, with data collected through in-depth interviews with youth and worship leaders, participatory observations during worship services, and document analysis of liturgy practices at a GMIM Imanuel Sawangan congregation in the Airmadidi Satu region. The findings indicate that participatory liturgy designed to suit cultural contexts and youth needs enhances discipline, responsibility, and internalization of Christian values among young participants. Moreover, the use of musical and narrative elements within the liturgy proves effective in attracting active participation and deepening faith appreciation. Innovative liturgical practices that integrate contemporary music with relevant messaging create worship experiences that foster not only spirituality but also positive social character development. This study underscores the necessity of developing youth liturgy as a tool for character education to meet contemporary challenges and strengthen the role of local churches in shaping a generation rooted in integrity and Christian values. The practical implications of this research may serve as a reference for other churches in developing effective and adaptive youth liturgy models.